Seedling Development and Evaluation of Genetic Stability of Cryopreserved Dendrobium Hybrid Mature Seeds - Galdiano, Renato Fernandes; Macedo Lemos, Eliana Gertrudes de [UNESP]; Faria, Ricardo Tadeu de; Vendrame, Wagner Aparecido (Humana Press Inc, 2014)
Vitrification, a simple, fast, and recommended cryopreservation method for orchid germplasm conservation, was evaluated for Dendrobium hybrid Dong Yai mature seeds. The genetic stability of regenerated seedlings was also evaluated using flow cytometry. Mature seeds from this hybrid were submitted to plant vitrification solution (PVS2) for 0, 0.5, 1, 2, 3, 4, 5, or 6 h at 0 A degrees C. Subsequently, they were plunged into liquid nitrogen (LN) at -196 A degrees C for 1 h and recovered in half-strength Murashige and Skoog culture medium (1/2 MS), and seed germination was evaluated after 30 days. Seeds directly submitted to LN did not germinate after cryopreservation. Seeds treated with PVS2 between 1 and 3 h presented the best germination (between 51 and 58 %), although longer exposure to PVS2 returned moderated germination (39 %). Germinated seeds were further subcultured in P-723 culture medium and developed whole seedlings in vitro after 180 days, with no abnormal characteristics, diseases, or nutritional deficiencies. Seedlings were successfully acclimatized under greenhouse conditions with over 80 % survival. Flow cytometry analysis revealed no chromosomal changes on vitrified seedlings, as well as seedlings germinated from the control treatment (direct exposure to LN). These findings indicate that vitrification is a feasible and safe germplasm cryopreservation method for commercial Dendrobium orchid hybrid conservation.
Keywords: Vitrification; Commercial orchid; Germplasm conservation; Flow cytometry